Increased plasma levels of damage-associated molecular patterns during systemic anticancer therapy in patients with advanced lung cancer - Inoue, Hiroyuki (Transl Lung Cancer Res, 2021)
BACKGROUND: Immunogenic cell death (ICD) characterized by the release of damage-associated molecular patterns (DAMPs) from dying cancer cells may contribute to the synergistic antitumor effect of cytotoxic chemotherapy combined with an immune checkpoint inhibitor. The kinetics of circulating DAMP levels in cancer patients have remained largely uncharacterized, however. METHODS: We evaluated the possible effects of various systemic anticancer therapy modalities on the kinetics of plasma DAMP concentrations in a prospective observational study of patients with advanced lung cancer. The plasma concentrations of high-mobility group box 1 (HMGB1), calreticulin (CRT), heat shock protein 70 (HSP70), annexin A1, and histone H3 were thus determined in 121 such patients at four time points during the first cycle of treatment. RESULTS: The mean of the maximum fold change in HMGB1, HSP70, or annexin A1 concentration observed during treatment was significantly greater than the corresponding baseline value (P<0.005). The maximum fold changes in HMGB1 and CRT concentrations tended to be associated with clinical response as evaluated by RECIST criteria, although the changes in the levels of these two DAMPs were not correlated, suggestive of differential induction mechanisms. Among the various treatment modalities administered, platinum-based combination or single-agent chemotherapy tended to elicit robust increases in the concentrations of HMGB1 and CRT. CONCLUSIONS: Serial monitoring of plasma revealed that systemic anticancer therapy increased the circulating levels of HMGB1 and CRT and that these changes tended to be associated with clinical response, suggesting that agents capable of releasing these DAMPs into plasma might induce ICD in advanced lung cancer patients.